The Psychic Sciences in France: Historical Notes on the Annales des Sciences Psychiques - Alvarado, Carlos S; Evrard, Renaud (Journal of Scientific Exploration, 2012)
This paper is an overview of aspects of the French journal Annales des Sciences Psychiques (ASP, 1891-1919) with emphasis on nineteenth century developments. The ASP was founded by Charles Richet and Xavier Dariex. The development of the journal was assisted both by the prestige and influence of Richet as a scientist and of Félix Alcan as a publisher. For the nineteenth-century period the journal emphasized cases and experiments over theories. Much of this was about spontaneous telepathy and physical mediumship. Some of the authors included in the pages of the ASP were Émile Boirac, Ernesto Bozzano, Albert de Rochas, Giovanni Battista Ermacora, Paul Joire, and Julian Ochorowicz. There were translations of the work of members of the Society for Psychical Research, such as Frederic W. H. Myers. In 1908 the ASP was affiliated with the Sociétè Universelle d’Études Psychiques, becoming its official publication. The ASP was important in establishing standards and in providing a forum for the development of psychical research in France.